Review of the notions of distributed ledger technologies and digital assets for harmonization of their joint use - A. V. Vlasov (Russian Journal of Economics and Law)
Objective: to analyze the transforming socio-economic relations of the new “digital normality”, to which end the task is solved of bringing into line the terminology used in business turnover between various participants in the digital assets market, in the practical financial activities of economic entities arising in a specific territory, in a certain legal field, and contained in the recommendatory technical documentation (standards).Methods: the article uses systematic and analytical approaches, logical and comparative methods.Results: despite the active use of distributed ledger technologies, theory and practice are currently characterized by a large number of legal and business definitions describing the organization of business processes in this area. Based on the analysis of scientific literature, the meaning of various terms of the digital economy was studied. In the course of studying technical terminology, such concepts as a distributed ledger, network nodes, blockchain, etc. were defined. The analysis of financial and economic terms is based on fintech definitions, such as digital asset, cryptocurrency, digital currency, digital financial asset, token, etc. The terms of the digital economy are considered from the perspective of so-called tokenomics, including such as token ecosystem, DLT user, DLT platform, decentralized application, etc.Scientific novelty: the terminology obtained was structured as a theoretical basis with a specification for the digital asset market and use in financial market reform.Practical significance: this review has been prepared: 1) to systematically familiarize the professional community with existing trends; 2) to harmonize socio-economic relations by developing common local recommendations (standards); 3) to develop the market for digital assets produced using distributed ledger technologies through understanding basic concepts.